Successful Management of A Caesarian Scar Pregnancy with Systemic Methotrexate Administration - Uluğ, Ulun; Demirören, Tanju; Has, Recep; Yüksel, Atıl; Bahçeci, Mustafa (Gynecology Obstetrics & Reproductive Medicine, 2006)
Cesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy in which the embryo implants into a repaired uterine section excision site. Prompt diagnosis is crucial because uterine rupture can lead to a life threatening hemorrhage. We report here the medical management of a CSP with multiple dose methotrexate and review the risk factors for CSP development and therapeutic approaches used to treat this condition.